Potential of Islamic films in the development of national creative industry / Nuruul Hidayah Mansor…[et.al] - Mansor, Nuruul Hidayah; Ayub, Mohamad Shafiei; Abdul Razak, Abdul Qayuum; Ramlan, Aini Faezah; Suyurno, S Salahudin; Md Sharipp, Muhammad Taufik (Faculty of Communication & Media Studies, 2019)
Current development shows that the industrial creative sector plays a role in the nation’s economic growth. Gross Domestic Product as issued by the Department of Statistics Malaysia reported that the manufacturing publishing sector, printing, re-making of media recording increased 2% for the nation’s GDP in 2013 compared to 1.6% in 2012. This development has opened bigger chances for local Islamic film industries to spur activities in the Islamic art and entertainment sectors because of their capabilities to become halal products which have high potentials to be commercialized into the international level. Integrated efforts to apply Islamic principles and values comprehensively in producing Islamic film products in Malaysia are expected to uphold the dignity of Islam and Malay culture values through film medias. Thus, Islamic film products are new and contemporary forms of preaching mediums suitable to current times and society.